Effect of a-Tocopherol on the Rate of Photohemolysis of Liposome Encapsulated Haemoglobin - A. Alfahhad, Marwan (Asian Journal of Chemistry, 2016)
Deformation of the liposome encapsulates the oxyhemoglobin upon exposure of liposome encapsulated haemoglobin to light wave and oxygen (photooxygenation conditions), due to the production of cholesterol hydroperoxide, can be controled depending on the results of this study. The present study suggests that a-tocopherol prohibits the production of cholesterol hydroperoxide in the liposome capsule, which if produced leads to a weakened capsule observed as a deformed Liposome Encapsutated Haemoglobin under the electron microscope.